Формирование личностных универсальных учебных действий во внеклассной работе - Nazipova G. K. (Студенческая наука XXI века, 2016)
The article considers the content, forms and methods of formation of personal universal educational actions at younger school age.
Keywords: универсальные учебные действия; самооценка; смыслообразование; самоопределение; формирование; Universal educational actions; self-determination; formation; нравственно-этическая ориентация; personal universal educational actions; meaning; moral-ethical orientation; self-esteem; личностные действия